Simulation and failure analysis of fibre-reinforced composite laminates under various load and boundary conditions / Mohamad Mali - Mali, Mohamad (2017)
Composite materials are desired in modern structures due to its various advantages. Nevertheless, the application of composites in structures is still limited by the difficulty in predicting their failure behaviour. Conventionally, predicting failure behaviour procedures involve with physical tests, which are expensive and tedious. Due to that, analytical method and simulation to predict experiment result are introduced. Nevertheless, to date, there is still lack of research related to finite element modelling and simulation to predict the failure behaviour of composite laminates under various load and boundary conditions. Moreover, no attempt has been done to simulate the failure behaviour of composite laminates under transverse sinusoidal loading and various boundary conditions using commercial software. Therefore, this study aims to simulate the deformation and failure behaviour of fibre-reinforced linear elastic, orthotropic, homogenous and unidirectional composite laminates under transverse sinusoidal loading and various boundary conditions using commercial software. The work has been organised according to four case studies, progressing from investigating the failure behaviour of composite laminates with ply orientation [04/O4/84]s under uniaxial load; composite laminates with ply orientation [0/0]s & [90/90]s , [+45/-45]s and [0/90]s under biaxial load; and to finally, composite laminates with ply orientation [0/90/90/0] under transverse sinusoidal load. In all cases, generally, convergence analysis and numerical validations were carried out first. For analytical approach, a MATLAB programme was written to compute the displacements, strains and stresses of the laminates based on the First Order Shear Deformation Theory (FSDT) under selected load and boundary conditions; as similar to ANSYS. For failure analysis, Maximum Stress and Tsai-Wu Failure criteria were employed to determine the failure loads. Failure curves for all four cases are plotted and each failure behaviour was analysed. In general, all the finite element models have been proved to be valid. Comparing the simulation and analytical approaches, the results (displacements, stresses and failure loads) for uniaxial and biaxial load are found close to each other, by maximum difference of 2%. For transverse sinusoidal load, the current finite element model is found to be accurate for simulating a thin and moderately thick laminate (aspect ratio; S > 10). The study has proved that the FE models are accurate and thus conforming that the results obtained using the FE commercial software (ANSYS) are valid. It also proves that the integration between FE simulation and analytical approaches can become an effective tool in investigating the failure behaviour of composite laminates. This study has contributed significantly to enhancing knowledge about the failure behaviour of fibre-reinforced composite laminates under various load and boundary conditions using commercial finite element software, ANSYS and analytical computation based on the mechanic of composite materials. This study is novel as to date, no study investigating the effects of boundary c